Perfomance of Agricultural Capital Formation in India: An Impact of AOA - Agarwal, Himanshu; Shailza (Journal of Commerce and Trade, 2014)
World Trade Organization (WTO), the modified transformation of GATT 1947 including new package of various agreements, has made easier way to flow the trade among the member countries. As India is an agro-prime country, Agreement on Agriculture (AOA) becomes very important and sensitive issue for India. But with trade openness factor some paradoxical things are included in this agreement like green box and blue box arrangement which exist especially in developed countries. Through this way developed countries may block the imports from the developing countries according their welfares without any objection of other countries. So Indian farmers are unable to compete with the cheap subsidized product of developed countries and finally they have no choice except low priced selling of their agricultural products. Thus this loss of income of farmers decreases the agricultural investment. We analyzed that the annual average of Gross Capital Formation (GCF) in agriculture & allied sectors as percentage of Gross Domestic Capital Formation (GDCF) and as percentage of Gross Domestic Product (GDP) decreased from 21.57% and 2.55% in pre WTO period to 6.22% and 2.16%, respectively, in post WTO period in India.